2008
DOI: 10.1523/jneurosci.1756-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Circuit Composed of CPEB-1 and c-Jun Controls Growth Hormone-Mediated Synaptic Plasticity in the Mouse Hippocampus

Abstract: Cytoplasmic polyadenylation element binding protein 1 (CPEB-1) resides at postsynaptic sites in hippocampal neurons in which it controls polyadenylation-induced translation. CPEB-1 knock-out (KO) mice display defects in some forms of synaptic plasticity and hippocampal-dependent memories. To identify CPEB-1-regulated mRNAs, we used proteomics to compare polypeptides in wild-type (WT) and CPEB-1 KO hippocampus. Growth hormone (GH) was reduced in the KO hippocampus, as were the GH signaling molecules phospho-JAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…As a consequence of its regulation of mRNA expression, CPEB mediates germ cell development (15,16), neuronal synaptic plasticity (17)(18)(19)(20), and cellular senescence (21)(22)(23)(24). Several observations suggest that CPEB might also be involved in the immune response.…”
mentioning
confidence: 99%
“…As a consequence of its regulation of mRNA expression, CPEB mediates germ cell development (15,16), neuronal synaptic plasticity (17)(18)(19)(20), and cellular senescence (21)(22)(23)(24). Several observations suggest that CPEB might also be involved in the immune response.…”
mentioning
confidence: 99%
“…CPEB knockout mice (44) have deficiencies in synaptic plasticity, particularly, theta burst-induced long-term potentiation (LTP) (1,51), as well as in particular forms of hippocampal-dependent memories (3). Some of these CPEB-related functions may be related at least in part to its ability to direct CPE-containing RNA transport in dendrites (16), in addition to its regulation of translation (51).…”
mentioning
confidence: 99%
“…It has also been shown that c-jun mRNA translation is regulated by CPEB and that growth hormone (GH) transcription via c-jun could mediate synaptic plasticity in the mouse hippocampus. 104 Interestingly, ARE-containing mRNAs are regulated by a polyadenylation/deadenylation mechanism both in the cytoplasm and in the nucleus. 49,104 It has been shown that CPEB possesses a self-perpetuating prion-like behavior in invertebrates, and that the aggregated form of CPEB remains activated for a long period of time upregulating cytoplasmic polyadenylation and translation locally in dendrites.…”
Section: Cis-elements Involved In Polyadenylation/deadenylationmentioning
confidence: 99%
“…104 Interestingly, ARE-containing mRNAs are regulated by a polyadenylation/deadenylation mechanism both in the cytoplasm and in the nucleus. 49,104 It has been shown that CPEB possesses a self-perpetuating prion-like behavior in invertebrates, and that the aggregated form of CPEB remains activated for a long period of time upregulating cytoplasmic polyadenylation and translation locally in dendrites. [105][106][107] Further studies are required to determine if there is a functional connection between CPEB prion-like structure and its translational regulatory functions in different organisms.…”
Section: Cis-elements Involved In Polyadenylation/deadenylationmentioning
confidence: 99%